2022
DOI: 10.1097/fjc.0000000000001204
|View full text |Cite
|
Sign up to set email alerts
|

A Novel circUBR4/miR-491-5p/NRP2 ceRNA Network Regulates Oxidized Low-density Lipoprotein-induced Proliferation and Migration in Vascular Smooth Muscle Cells

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Moreover, reduced expression of miR-140-5p but enhanced miR-424(322) and miR-146-5p expression can be detected in whole blood samples from PAH patients, suggesting their diagnostic significance (113,114,116). Additionally, circ-UBR4 and miR-29a, as diagnostic biomarkers, are increased in serum from atherosclerosis patients (75,(77)(78)(79)82).…”
Section: Diagnostic Indicators Of the Ups Involving Ncrnasmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, reduced expression of miR-140-5p but enhanced miR-424(322) and miR-146-5p expression can be detected in whole blood samples from PAH patients, suggesting their diagnostic significance (113,114,116). Additionally, circ-UBR4 and miR-29a, as diagnostic biomarkers, are increased in serum from atherosclerosis patients (75,(77)(78)(79)82).…”
Section: Diagnostic Indicators Of the Ups Involving Ncrnasmentioning
confidence: 97%
“…This is particularly noteworthy that circRNA, as an emerging ncRNA, has received much attention in recent years. The mechanism is that circRNAs are involved in CVD progression by sponging miRNAs and regulating downstream proteins (circRNA/miRNA/ubiquitin ligase or deubiquitinating enzymes/ protein axis) via ubiquitination, for example, circDLGAP4/miR-143/HECTD1 axis improved stroke (89), circ-UBR4/miR-637/ FOXO4, circ-UBR4/miR-107/ROCK1, circ-UBR4/miR-491-5p/ NRP2, circ-UBR4/miR-185-5p/FRS2, and circ-CHFR/miR-214-3p/PAPPA axes as well as inhibition of circ_USP36/miR-197-3p/ROBO1 axis could ameliorate atherosclerosis (75)(76)(77)(78)(79)(80)(81), circ-HECTD1/miR-133b/TRAF3 and circ_HECTD1/miR-27a-3p/ FSTL1 axes as well as inhibition of circNfix/Nedd4l/Ybx1 and circNfix/miR-214/Gsk3b axes could reduce myocardial infarction and CVD (49,94,95), circ-sh3rf3/sh3rf3/GATA-4/miR-29a alleviated cardiac fibrosis (71). On the second level, some ubiquitin ligase mimics or inhibitors serve as therapeutic targets, providing new perspectives for the treatment of CVDs.…”
Section: Therapeutic Target Of Ups and Ncrnasmentioning
confidence: 99%
“…Previous studies have reported decreased expression of miR‐491‐5p in atherosclerotic plaque tissues and serum samples from patients with AS 19,20 . miR‐491‐5p exerts a protective role in AS development by inhibiting the oxidative stress and inflammatory responses of THP‐1 macrophages via MMP‐9 and suppressing the cellular proliferation and migration of vascular smooth muscle cells 19–22 . A recent study revealed that miR‐491‐5p is associated with the protective effect of circ_0003204 gene silencing on ox‐LDL‐induced HUVECs injury 23 .…”
Section: Introductionmentioning
confidence: 99%
“…19,20 miR-491-5p exerts a protective role in AS development by inhibiting the oxidative stress and inflammatory responses of THP-1 macrophages via MMP-9 and suppressing the cellular proliferation and migration of vascular smooth muscle cells. [19][20][21][22] A recent study revealed that miR-491-5p is associated with the protective effect of circ_0003204 gene silencing on ox-LDL-induced HUVECs injury. 23 Thus, miR-491-5p may exert a protective role in AS development, however, the mechanisms underlying its actions remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Vital modulators of ox-LDL-evoked VSMC migration and proliferation, including circular RNAs (cir-cRNAs) and proteins, are under exploration for the moment. 4,6,7 Elucidating the functions of these regulatory molecules will provide a new opportunity for developing better interventions in AS.…”
Section: Introductionmentioning
confidence: 99%